Rebellion In The Poem Howl By Allen Ginsberg - Aisyah Aisyah; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2021)
This research aims to analyze the types of rebellion principle used and how the rebellion portrayed used in the poem Howl by Allen Gisnberg. The data source used in this research is the poem Howl. In analyzing the data, the writer used a qualitative descriptive research method through a sociological approach. The data were obtained by using reading, collecting, and analyzing techniques and to classify the types of rebellion principle in the poem by Jhon Lewis Gillin and Jhon Philip Gillin’s theory. The result of this research were 26 data that contain types of rebellion principle where 7 data of assimilation, 2 data of accommodation, 2 data of acculturation, 8 data of contravention, 4 data of competition and 3 data of conflict. There are 6 types with 26 data and an explanation of rebellion portrayed in this research poem, but the types and portrayed that are more prominent are negative because the researcher finds a lot of war, capitalism, consumerism, deceit, torture, and murder physically and mentally. Evil America has turned the lives of the lower classes into a terrible and nightmare.